Accounting Information System for Room Rental Income Trends Using the Common Size Method at Grand Dian Boutique Hotel Cirebon - Suwandi, Suwandi; Nas, Chairun; Noviyanti, Kiki (Asosiasi Dosen Akuntansi Indonesia, 2022)
The purpose of this study is to design an accounting information system for Room Rental Income Trends Using the Common Size Method at Grand Dian Boutique Hotel Cirebon, so that management can find out the rental income of each hotel room. The research method used is the waterfall method, where this method can explain the research steps systematically and sequentially in building an application. The object of this research is the Grand Dian Boutique Hotel Cirebon. The results of this study are an accounting information system application that can make room rental payment data, analysis of hotel room rental income using the common size method and report on hotel room rental income trends.